Монгол улсын Их Хурлын тамга, тэмдэгийн түүхээс - Өлзийдолгор, Дарьсүрэн (Historia Mongolarum, 2003)
The article deals with the seals of the State Great Khural and state symbols in the last century. It illustrates the major changes of the state symbols and seals since the declaration of the Mongolian republic and new Constitution of Mоngolia in 1924.